3- Le Choix Rationnel - Nyerere, Julius Κ. Nyerere (Africa Development, 1977)
In their struggle for independence, liberty, justice and well-being of all their inhabitants, the Third World countries are confronted with the choice between the two existing socio-economic systems : capitalism and socialism. In this article, the author discusses the nature, the purpose and the determinants of this choice. In so doing, he analyses each of these systems. Under a capitalist system the purpose of production and distribu tion is the making of profit for those who own the means of produc tion and exchange, the need for goods is subsidiary to the profit invol ved in making them. Therefore, the owner of the machines and equip ment used in production is the one who determines whether there shall be any production, and of what kind, and in what quantity. Neither the men who provide the labour for the productions, nor the men who need the goods which could be produced, have any say in these decisions. Under capitalism, money is King. He who owns wealth owns also power. He has power over all the workers who he can em ploy or not, and power over the government which he can paralyse by withholding vital production, or sabotage by the manipulation of men and machines. And this economic power is more and more concentra ted in very few hands, since mass production techniques make small units uneeconomic : they go bankrupt in an attempt to compete with the giants, or else sell out to a larger business. Therefore, instead of having a very large number of small capitalists, we have a very small number of large capitalists. This development is part of the dynamic of capitalism, which is fighting system : each capitalist enterprise survives by successfully fighting other capitalist enterprises. And the capitalist system as a whole survives by expansion, that is, by exten ding its area of operations and, in the process, eradicating all restraints upon it, and all weaker systems of society. Given the fact that nowadays there are no capitalists from our countries who can successfully compete with foreign concerns, the Third World capitalism, should this path to development be chosen, would have no choice except to cooperate with external capitalism, as a very junior partner. Otherwise, it would be strangled at birth. We cannot develop capitalism in our countries without foreign capitalists, their money and their management expertise. And these foreign capi talists will invest in Third World countries only if, when, and to the extent that, they are convinced that to do so would be more profitable to them than any other investment. Development through capitalism means that the Third World nations have to meet conditions laid down by others — by capitalists of other countries. And if we agreed to their conditions, we should have to continue to be guided by them or face the threat of the new enterprises being run down, money and skills, being withdrawn, and of other economic sanctions being applied against us. In fact, a reliance upon capitalist development means that we give to others the power to make vital decisions about our economy. The kind of economic production we shall undertake ; the location of factories, offices and stores ; the amount of employment available in any area ;and even the kind of taxation system we adopt, all these matters will be determined by outsiders. In addition, capitalism does not only imply a fight between capi talists, with the developing nations' capitalists inevitably being worsted. It also involves a permanent fight between capitalists on one side and workers on the other. Thus, capitalism automatically brings with it the development of two classes of people : a small group whose owner ship of the means of production brings them wealth, power and privi lege ; and a very much larger group whose work provides that wealth and privileges. The one benefits by exploiting the other, and a failure in the attempt to exploit leads to a breakdown of the whole system with a consequent end to all production. The exploitation of masses is, in fact, the basis on which capitalism has won the accolade for having solved the problem of production. There is no other basis on which it can operate. For if the workers even succeeded in obtaining the full benefits of their industry, then the capitalist would receive no profit and would close down the enterprise. Development through capitalism is thus basically incompatible with human dignity and self-respect for all, with equal freedom for all inhabitants of the society. Because Socialism can be compatible with our aspirations, by adopting socialist policies it is possible for us to maintain our inde pendence and development towards human dignity for all our people. For the basis of socialist organization is the meeting of people's needs, not the making of profit. The decision to devote the nation's resources to the production of one thing rather than another is made in the light of what is needed, not what is most profitable. Furthemore, such deci sions are made by the people through their responsible institutions : their own government, their own industrial corporations, their own commercial institutions. They are not made by a small group of capi talists, eitheir local or foreign ; and the question of foreign domination through economic ownership is thus excluded. Further the workers of the nation can receive directly or indirectly — the full fruits of their industry ; there is no group of private owners which constantly appropriates a large proportion of the wealth produced. In spite of many difficulties that face a Third World country which chooses the socialist alternative of development, the author strongly proposes the adoption of this alternative, since by so doing, we can develop ourselves in freedom, and towards those conditions which allow dignity and self-respect for everyone of our citizens